Using Standardized Patients to Assess Hospitalist Communication Skills. Issue 7 (1st July 2017) - Chang, Dennis T.; Mann, Micah; Sommer, Terry; Fallar, Robert; Weinberg, Alan; Friedman, Erica
Abstract : Standardized patients (SPs) have been used to assess communication skills in undergraduate medical education, but no published studies describe the use of SPs in assessing practicing physicians on their communication skills. In this study, done with 23 hospitalists at a large urban academic hospital, 3 SP scenarios, daily rounding, discharge, and interacting with a difficult patient, were created. After each encounter, each hospitalist reviewed their videotape and received feedback from their SP based on a checklist that had 3 core domains: Listen, Courtesy and Respect, and Explain. These domains correlated with the 3 questions in the Hospital Consumer Assessment of Healthcare Providers and Systems survey that relate to doctors. Hospitalists performed significantly better in the Listen domain, with a mean percent adequate score of 90.2% (95% confidence interval [CI], 72.2%‐100%; P < 0.05), and significantly worse in the Explain domain, with a mean percent adequate score of 65.0% (95% CI, 49.2%‐83.6%; P < 0.05). Checklist items in the Explain domain that were most commonly not performed adequately were summarizing information at the end of the encounter, teach back, encouraging additional questions, managing team and self‐up, setting expectations about length of stay, and timing of tests. After the SP encounters, hospitalists felt more confident in their communication skills. SPs can be used to assess and give feedback to hospitalists and increase confidence in several aspects of communication.